PATRONS OF OTTOMAN MOSQUES IN GREECE RECONSIDERED IN LIGHT OF THE IERAPETRA MOSQUE OF CRETE - Ameen, Ahmed (Journal of Islamic Architecture, 2019)
TThe subject of this paper is based on a reconsideration of patrons of Ottoman mosques in Greece in light of the analyzed study of the Ierapetra Mosque of the island of Crete. This paper draws a layout of the Ierapetra city under the Ottomans based on the relevant sources with particular reference to the salnames and old photographs. It examines in details about the architecture, the inscriptions, and the historical context of Ierapetra mosque. This paper also corrects the reading of some inscriptions and proposes reading for some Arabic inscriptions for the first time. Based on a survey by the author conducted between 2006 and 2016, there are around eighty Ottoman historical mosques in Greece that still exist. It concludes that the Ierapetra mosque is a notable example with its architecture, inscriptions, and fountain. Moreover, it is one of the rare cases in Greece that were built by the contribution of the Muslim community of the city.Â